2009
DOI: 10.1007/s00542-009-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of micro injection molded weld line strength with ultrasonic oscillation

Abstract: Weld lines are the unfavorable defect not only in normal injection molding process but in micro injection molding process. In this study, polypropylene (PP) was chosen as the processing material and a micro dog-bone tensile test sample was selected as the objective part. The micro tensile part was prepared by the double gate injection mold. An ultrasonic generator was integrated in this mold in order to investigate the effect of ultrasonic oscillation on the micro injection molded weld line strength. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Ultrasonic processing technology, as a novel molding processing technology, has been widely used in recent years for the injection molding, extrusion molding, and compression molding of polymers [9,10]. Despite different ways of applying ultrasonic energy, studies have found that ultrasounds can affect the microstructure filling performance [11], change the material properties [12], affect the extrusion swelling [13], improve the weld line strength of the plastic parts [14], and reduce the interface friction during ejection [15]. However, current studies are mainly based on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic processing technology, as a novel molding processing technology, has been widely used in recent years for the injection molding, extrusion molding, and compression molding of polymers [9,10]. Despite different ways of applying ultrasonic energy, studies have found that ultrasounds can affect the microstructure filling performance [11], change the material properties [12], affect the extrusion swelling [13], improve the weld line strength of the plastic parts [14], and reduce the interface friction during ejection [15]. However, current studies are mainly based on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the application of ultrasound technology in polymer micro-injection molding has not been systematically reviewed, the names of similar technologies have not yet been unified: ultrasonic injection molding (UIM) [ 18 ], ultrasonic vibration micro-injection mold (UVMIM) technology [ 38 ], ultrasonic-assisted injection molding (UAIM) [ 39 ], but the common point of this technology is that the ultrasonic action is aimed at the polymer melt, improving its fluidity and achieving high replication and quality requirement of parts. Polymer plasticization, metering, injection, and other processes rely on existing micro-injection-molding machines (ARBURG [ 31 , 40 ], FANUC [ 14 , 41 , 42 ], BOY [ 43 ], Wittmann-Battenfeld [ 44 ]). Considering the difference between micro-injection molding and injection molding and the auxiliary effect of ultrasound, this kind of technology can be classified as ultrasound-assisted micro-injection molding (UAMIM).…”
Section: Ultrasound-assisted Micro-injection Moldingmentioning
confidence: 99%
“…Owing to the advantages of thermoplastic multicomponent injection moulding, such as reduced assembly expenditure and manufacture of multicomponent moulded parts, [22][23][24] efforts are undertaken to transfer this technology to PIM. However, this gives rise to additional process technology problems, in particular by shrinkage due to sintering.…”
Section: Multicomponent Pimmentioning
confidence: 99%